Reduction in risk of contrast-induced nephropathy in patients with chronic kidney disease and diabetes mellitus by enhanced external counterpulsation - Zeng, Chun-Mei; Zhao, Yan-Mei; Zhong, Xin-Jing; Wu, Zi-Jia; Bai, Jing; Qiu, Shi-Yu; Li, Yi-Yi (Frontiers in Endocrinology, 2022)
Objective To evaluate the efficacy of enhanced external counterpulsation (EECP) in the prevention of contrast-induced nephropathy (CIN) in patients with combined chronic kidney disease (CKD) and diabetes mellitus (DM) by comparing the changes in renal function-related indicators in patients before and after coronary angiography (CAG) or percutaneous coronary intervention (PCI). Methods There were 230 subjects consecutively included in the study. Of these, 30 cases with DM underwent rehydration therapy, and 200 cases underwent EECP therapy in addition to rehydration therapy, comprising 53 patients with DM and 147 patients without. All the patients were tested to measure the renal function indicators before and after CAG/PCI. Results The postoperative results of blood urea nitrogen (BUN), serum creatinine (Scr), estimated glomerular filtration rate (eGFR), B2 microglobulin, and high-sensitivity C-reactive protein in the three groups showed a statistically significant difference (P < 0.05). After EECP therapy, patients with DM showed a significant decrease in BUN (9.1 ± 4.2 vs. 7.2 ± 3.0, t = 3.899, P < 0.001) and a significant increase in eGFR (41.5 ± 12.7 vs. 44.0 ± 15.6, t = −2.031, P = 0.047), while the patients without DM showed a more significant difference (P < 0.001). Patients with DM showed a lower percentage of elevated Scr (66.7% vs. 43.4%, P = 0.042), a higher percentage of elevated eGFR (30.0% vs. 52.8%, P = 0.044), and a lower incidence of CIN (16.7% vs. 3.8%, P = 0.042) after EECP therapy. Conclusion Treatment with EECP can reduce Scr in patients with combined CKD and DM post CAG/PCI, increase eGFR, and decrease the incidence of CIN.